Marginality and competitive advantage: The implications of the opening of the CBDs for Chinese businesses - Linda Human; K. Y. Fok; N. Chom (South African Journal of Business Management, 1987)
The opening of the CBDs (central business districts) as free trading areas has important implications for the areas of business management, sociology and politics inasmuch as this move represents a significant deviation from past government policies. Before the Johannesburg CBD was declared open for free trading, the Chinese operating within the CBD were afforded the same protection as whites by the barriers imposed upon other 'non-white' traders. At the same time, and unlike whites, the Chinese could also move into 'non-white' trading zones without difficulty. The Chinese thus appeared to be operating from a position of strategic advantage, a position which could be attributed to their marginal status in South African society. This article examines the extent to which their marginal position has provided a competitive advantage for the Chinese traders in the Johannesburg CBD as well as the attitudes of these businessmen to the opening of the CBD to all race groups.
Keywords: 650